Pressure dependence of elastic and dynamical properties of zinc-blende ZnS and ZnSe from first principle calculation - Wang, H.Y.; Cao, J.Y.; Huang, X.Y.; Huang, J.M. (Condensed Matter Physics, 2012)
The density-functional theory (DFT) and density-functional perturbation theory (DFPT) are employed to study the pressure dependence of elastic and dynamical properties of zinc-blende ZnS and ZnSe. The calculated elastic constants and phonon spectra from 0GPa to 15GPa are compared with the available experimental data. Generally, our calculated values are overestimated with experimental data, but agree well with recent other theoretical values. The discrepancies with experimental data are due to the use of local density approximation (LDA) and effect of temperature. In this work, in order to compare with experimental data, we calculated and discussed the pressure derivatives of elastic constants, the pressure dependence of dynamical effect charge, and mode Grüneisen parameter at Γ. Теорiя функцiоналу густини (DFT) i теорiя збурень функцiоналу густини (DFPT) застосовується до вивчення залежностi вiд тиску пружних i динамiчних властивостей цинкової обманки ZnS i ZnSe. Розрахованi пружнi сталi i фононнi спектри вiд 0 GPa до 15 GPa порiвнюються з наявними експериментальними даними. Взагальному, нашi розрахованi значення є переоцiненi в порiвняннi з експериментальними, але узгоджуються добре з iншими теоретичними значеннями. Розбiжностi з експериментальними даними є через використання наближення локальної густини (LDA) i впливу температури. Для порiвняння з експериментальними даними, ми обчислюємо i обговорюємо похiднi за тиском вiд пружних сталих, залежнiсть вiд тиску динамiчного ефективного заряду i параметр Грюнайзена при Γ.